The Eksistensi Permainan Tradisional Di Era Moderen Dan Kaitannya Dengan Perkembangan Motorik Kasar Anak - Riansyah, Wahyu (STKIP Pasundan, 2022)
This paper aims to see the extent of the existence of traditional games among children in modern times today. This paper also collects the extent of children's knowledge about traditional games or games native to certain areas, so that nowadays children are expected to be able to know how important traditional games are in process of growing children’s gross motor skills. In this research, the method used is descriptive qualitative method. Then the school as a medium of socialization for children should be able to provide knowledge about traditional games, or even provide special time for children to practice these games. So that among the children there is an agreement to be able to play congklak, gobak sodor, or jump rope at home.